The Effect of Emotional Intelligence on Intention To Leave Through Organizational Commitment - Karambut, Christien Adriani; Makapedua, Jacob T.S; Sundah, Daisy I. E.; Rumimper, Grace J. S. N. (Wacana Journal of Social and Humanity Studies, 2024)
One of the current human resource management challenges is dealing with the behavior of employees who wish to move to another place because, in recent years, this phenomenon has continued to occur. The high rate of turnover intention also appears in several private and public hospitals in Malang Raya. This study aims to examine the effect of emotional intelligence on the intention to leave through nurses' organizational commitment. This type of research is explanatory. The research location is in private, public hospitals in Malang Raya (Malang City, Malang Regency, and Batu City). Using proportional random sampling, there were as many as 253 nurses with a response rate of 84.3%. The analysis method is descriptive statistics using the General Structured Component Analysis (GSCA) approach. The findings of this study indicate that emotional intelligence is a predictor of increasing organizational commitment and reducing intention to leave. They can cope with stress and work pressure more effectively, increasing job satisfaction and reducing the urge to leave the organization. The ability to understand, recognize, and manage emotions in themselves and others makes it easier for them to work with colleagues and superiors. Positive work relationships strengthen their attachment to the organization. Emotional intelligence helps reduce prolonged conflict and increases communication effectiveness, ultimately making the work environment more conducive. Keywords: emotional intelligence, work-life balance, organizational commitment, intention to leave